Perioperative pulmonary aspiration is infrequent and low risk in pediatric anesthetic practice - Kelly, Christopher J.; Walker, Robert W. M. (Pediatric anesthesia, 2015)
Summary Recent studies have reported perioperative pulmonary aspiration in pediatric practice to be an uncommon problem associated with low morbidity and mortality. This paper examines the recent publications in both the adult and pediatric literature and looks at some of the potential risk factors involved, both patient and anesthetic, in the development of aspiration of gastric contents. We also look at the risk of severe morbidity following pulmonary aspiration and speculate on possible reasons behind the assertion that pulmonary aspiration in pediatric anesthetic practice is rare and a low‐risk event.